Angiographic flow velocity predicts lower limb outcomes after endovascular therapy: Application of the frame count method. (February 2022) - Ito, Naruhiko; Hishikari, Keiichi; Yoshikawa, Hiroshi; Tsujihata, Shihoko; Abe, Fumiyuki; Kanno, Yoshinori; Iiya, Munehiro; Murai, Tadashi; Hikita, Hiroyuki; Takahashi, Atsushi; Yonetsu, Taishi; Sasano, Tetsuo
Introduction: Several factors related to lesion characteristics and endovascular therapy (EVT) procedures have been reported to affect primary patency after EVT. However, it is unknown why these factors were associated with primary patency. We hypothesized patency failure was related to poor blood flow in affected arteries. Methods: This retrospective study included 131 consecutive patients who had received EVT with bare metal stents for peripheral artery disease caused by femoropopliteal artery lesions. Based on the tertile post-EVT flow velocity of the superficial femoral artery (SFA), patients were divided into high ( n = 43), middle ( n = 44), and low ( n = 44) flow velocity groups. Flow velocity was measured using the frame count method. We measured incidence of major adverse limb events (MALE), composed of target lesion revascularization (TLR), non-TLR, and major amputation. Results: At a median follow-up period of 22.7 months, MALE had occurred in 7 (16.3%), 10 (22.7%), and 29 (65.9%) of patients from the high, middle, and low SFA flow velocity groups, respectively ( p < 0.001). Kaplan–Meier analysis showed incidence of MALE was significantly higher in the patients of low SFA flow velocity (log-rank test χ 2 = 38.8, p < 0.001). Multivariate analysis found low SFA flow velocity to be an independent predictor for MALE (hazard ratio: 4.42; 95% CI: 2.27 to 8.60; p < 0.001) as was ankle–brachial index. Conclusion: Post-EVT SFA flow velocity for femoropopliteal artery lesions treated with bare metal stents is an independent predictor of limb patency. The frame count method for assessing arterial flow velocity is convenient and has potential for wide applications in EVT.